Transactivated and chemically inducible gene expression in plants. - Moore, I; Samalova, M; Kurup, S (2006)
Several vector systems are available for tissue-specific transactivation or chemical induction of transgene expression in plants. The choice facing researchers is which promoter system to commit to as this determines the range and characteristics of the expression resources available. The decision will not be the same for all species or applications. We present some general discussion on the use of these technologies and review in detail the properties in various (mainly angiosperm) species of the most promising: mGal4:VP16/UAS and pOp/LhG4 for transactivation, and the alc-switch, GVE/VGE, GVG, pOp6/LhGR, and XVE systems for chemical induction.